Hepatitis C virus fitness can influence the extent of infection-mediated epigenetic modifications in the host cells - García-Crespo, Carlos; Francisco-Recuero, Irene; Gallego, Isabel; Camblor-Murube, Marina; Soria, María Eugenia; López-López, Ana; de Ávila, Ana Isabel; Madejón, Antonio; García-Samaniego, Javier; Domingo, Esteban; Sánchez-Pacheco, Aurora; Perales, Celia (Frontiers in Cellular and Infection Microbiology, 2023)
Cellular epigenetic modifications occur in the course of viral infections. We previously documented that hepatitis C virus (HCV) infection of human hepatoma Huh-7.5 cells results in a core protein-mediated decrease of Aurora kinase B (AURKB) activity and phosphorylation of Serine 10 in histone H3 (H3Ser10ph) levels, with an affectation of inflammatory pathways. The possible role of HCV fitness in infection-derived cellular epigenetic modifications is not known. Here we approach this question using HCV populations that display a 2.3-fold increase in general fitness (infectious progeny production), and up to 45-fold increase of the exponential phase of intracellular viral growth rate, relative to the parental HCV population. We show that infection resulted in in a HCV fitness-dependent, average decrease of the levels of H3Ser10ph, AURKB, and histone H4 tri-methylated at Lysine 20 (H4K20m3) in the infected cell population. Remarkably, the decrease of H4K20m3, which is a hallmark of cellular transformation, was significant upon infection with high fitness HCV but not upon infection with basal fitness virus. Here we propose two mechanisms ─which are not mutually exclusive─ to explain the effect of high viral fitness: an early advance in the number of infected cells, or larger number of replicating RNA molecules per cell. The implications of introducing HCV fitness as an influence in virus-host interactions, and for the course of liver disease, are warranted. Emphasis is made in the possibility that HCV-mediated hepatocellular carcinoma may be favoured by prolonged HCV infection of a human liver, a situation in which viral fitness is likely to increase.